Spectral changes in the leaves of barley plant due to phytoremediation of metals :results from a pot study - Rathod, Paresh H. (2020)
This research studied the changes in leaf reflectance spectra (350-2500 nm) due to metal phytoextraction into barley plants grown in metal-spiked soils (3 levels of Cd, Pb, As and their metal-mixture treatments). Growth of barley was adversely affected due to 100 mg As kg−1 and metal-mixture (10 Cd+150 Pb+100 As; mg kg−1) treatments. Metal phytoextraction were in order of: root >straw ≥leaves >grains. Results of reflectance spectra of leaves show the influence of As-treatment only, causing spectral changes in visible and infrared domains mostly, as apparent from the significant correlation between leaf-As and leaf-spectra. Chlorophyll and water stress indices and band depths analyses showed significant correlations to leaf-As, and can be used to distinguish metal-stressed plants. Finally, regression models demonstrate the potential use of hyperspectral reflectance data to monitor plant health during phytoremediation process and to estimate leaf-As in barley, particularly in this study.cs of animal movement.